Possible improvements in the action of some rust converters (2001)
ABSTRACT: The anticorrosive properties of 18 rust converters were investigated. The corrosion products on pre-rusted mild steel samples and their mechanisms of reaction with the converters were studied. Accelerated corrosion tests were also performed. It was found that a mixture of tertbutyl and isopropyl alcohol facilitates penetration and adherence of the converters. Nevertheless, the converter does not reach the metal surface and the reactions are largely restricted to the outer layers. This circumstance, and the fact that anticorrosive properties are accelerated test-dependent, were considered as important reasons for the understanding of the contradictory results found with these products.